Eco-feasibility study of a distributed power generation system driven by renewable green energy sources. Issue 2 (15th June 2022) - Abbassi, Abdelkader; Ben Mehrez, Rached; Abbassi, Rabeh; Jerbi, Houssem; Saidi, Salem; Jemli, Mohamed
ABSTRACT: This paper improves a previously optimization approach to accomplish an enhanced total cost of electricity (TCE). Based on the integration of many energy deposits for supporting the primary Renewable Green Energy Source (RGES), the whole system is modeled with improved manner, which contributes to well achieve a more comprehensive write-up of the studied formulation problem. To decrease the TCE of the system containing a photovoltaic/wind turbine with battery storage system, the so-called virus colony search (VCS) algorithm is developed. Hence, the association of a lead-acid battery devoted to absorption of the high fluctuations is essential, which can contribute to the operational safety of the system. Thus, techno-economic analysis and cost-effectiveness evaluation are investigated. By depicting TCE as a key factor in this study and compared with other conventional algorithm, a reliability analysis is elaborated in accordance with the lowest cost of electricity. The obtained results prove a high level of economic feasibility in agreement with some evaluation criteria by achieving the lowest TCE. The benefit of the optimization based on VCS algorithm is successfully demonstrated in accordance with highest reliability by a significant saved cost. The results of the optimization display that savings in TCE is 14, 792  $ as compared to the calculation process without using VCS algorithm.